Proteomics in Argentina - limitations and future perspectives: a special emphasis on meat proteomics - Fadda, Silvina G. (2015)
Argentina is one of the most relevant countries in Latin America, playing a major role in regional economics, culture and science. Over the last 80 years, Argentinean history has been characterized by several upward and downward phases that had major consequences on the development of science in the country and most recently on proteomics. In this article, we characterize the evolution of Proteomics sciences in Argentina over the last decade and a half. We describe the proteomics publication output of the country in the framework of the regional and international contexts, demonstrating that Argentina is solidly anchored in a regional context, showing results similar to other emergent and Latin American countries, albeit still far from the European, American or Australian realities. We also provide a study-case-study on the importance of Proteomics to a specific sector in the area of food science: the use of bacteria of technological interest, highlighting major achievements obtained by Argentinean proteomics scientists. Finally, we provide a general picture of the endeavors being undertaken by Argentinean Proteomics scientists and their international collaborators to promote the Proteomics-based research with the new generation of Scientists and PhD students in both Argentina and other countries in the Southern cone.